2014
DOI: 10.1007/s12036-014-9251-7
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Wavelength Variability Properties of Fermi Blazar S5 0716+714

Abstract: S5 0716+714 is a typical BL Lacertae object. In this paper we present the analysis and results of long term simultaneous observations in the radio, nearinfrared, optical, X-ray and γ-ray bands, together with our own photometric observations for this source. The light curves show that the variability amplitudes in γ-ray and optical bands are larger than those in the hard X-ray and radio bands and that the spectral energy distribution (SED) peaks move to shorter wavelengths when the source becomes brighter, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Cross-correlations of the fluxes from ground-based and satellite instruments at a variety of wavebands have been carried out for segments of the data sets in a number of recent papers, e.g. [9], and characteristic time scales identified using structure functions and periodograms [10]. This work identifies complex relationships which are overall consistent with the production of flaring by a common disturbance which propagates outward in the jet with time.…”
Section: Variability Since the Launch Of Fermimentioning
confidence: 99%
“…Cross-correlations of the fluxes from ground-based and satellite instruments at a variety of wavebands have been carried out for segments of the data sets in a number of recent papers, e.g. [9], and characteristic time scales identified using structure functions and periodograms [10]. This work identifies complex relationships which are overall consistent with the production of flaring by a common disturbance which propagates outward in the jet with time.…”
Section: Variability Since the Launch Of Fermimentioning
confidence: 99%
“…The X-ray spectrum of the continuum emission appears to have a concave shape, displaying a transition from the synchrotron to the inverse-Compton emission components (see e.g., [9,10]). S5 0716+714 has also been detected by γ-ray instruments such as the Compton EGRET, AGILE, Fermi-LAT satellites and also by the MAGIC Cherenkov telescope (see, e.g., [11][12][13][14] and references therein). In particular, there have been numerous optical microvariability studies of S5 0716+714 which reported many interesting results, including achromatic behavior, red noise-type power spectra, and in some cases, correlation between flux and polarization degree [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%